California Rising : the Life and Times of Pat Brown. - Rarick, Ethan, 1964- (University of California Press, 2005)
It is now commonplace to say that the future happens first in California, and this book, the first biography of legendary governor Edmund G. "Pat" Brown, tells the story of the pivotal era when that idea became a reality. Set against the riveting historical landscape of the late fifties and sixties, the book offers astute insights into history as well a fascinating glimpse of those who charted its courseincluding Ronald Reagan, John F. Kennedy, and the Brown family dynasty. Ethan Rarick mines an impressive array of untapped sourcessuch as Pat Brown's diary and love letters to his w.